The Description of Characteristic Facebook Social Networking and Sleep Quality in Medical Students - Elly Tania; Evalina Asnawi; Willy Steven; Meiliana Meiliana; Zulfia Syarif; Dian Yulita Sarapang (Jurnal MedScientiae, 2023)
Poor sleep quality that occurs in medical students is known to be quite high, one of the factors is the use of social networks. Objective is to determine a Description of Characteristic Facebook Social Networking and Sleep Quality in Medical Student’s Faculty of Medicine Krida Wacana Christian University, Class of 2015. This study used a descriptive method with a cross sectional approach with a sample of 72 respondents. The research sample was taken by simple random sampling. The study was conducted by distributing questionnaires consisting of 3 parts Pittsburgh Sleep Quality Index (PSQI), user character, and Facebook usage. Results: A total of (45.8%) aged 21 years and dominated by female sex (73.6%) and as many as (86.1%) experienced poor sleep quality. Conclusion: in this study only illustrates the character of the use of social networking facebook and sleep quality of medical students, so that in future research it is expected to be able to connect other factors related to the use of social networking and sleep quality in medical students.